Reparative Mineralized Tissue Characterization by Different Bioactive Direct Pulp-capping Agents - Mrunal Shinde; Varsha Pandit; Sarita Singh; Aniket Jadhav; Sarah Marium; Smita Patil (Wolters Kluwer Medknow Publications, 2024)
The aim of direct pulp caping (DPC) is to support the formation of mineralized tissue and encourage pulp healing by placing a dental biomaterial directly over the exposed pulp. The era of vital pulp therapy has been influenced by the introduction of various pulp-capping materials. Emphasis has shifted from the "doomed" organ concept of an exposed pulp to one of hope and recovery; this comprehensive review thus discusses the ability of different direct pulp-capping materials to form a dentin bridge. Furthermore, this review will discuss the quality and quantity of dentinal bridge formation by different pulp-capping agents.